2013
DOI: 10.1093/cid/cit528
|View full text |Cite
|
Sign up to set email alerts
|

Iron Supplementation in HIV-Infected Malawian Children With Anemia: A Double-Blind, Randomized, Controlled Trial

Abstract: ISRCTN-62947977.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 20 publications
3
41
0
1
Order By: Relevance
“…Haemoglobin at end of treatment was similarly reported in a single study, Giovannini 2006, and was higher with iron and folate, mean difference 0.90 g/dL (95% CI 0.51 to 1.29; 124 children Analysis 2.5). The RR for anaemia at end of treatment was 0.49 (0.25 to 0.99; three trials, 633 children, Analysis 2.6).…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Haemoglobin at end of treatment was similarly reported in a single study, Giovannini 2006, and was higher with iron and folate, mean difference 0.90 g/dL (95% CI 0.51 to 1.29; 124 children Analysis 2.5). The RR for anaemia at end of treatment was 0.49 (0.25 to 0.99; three trials, 633 children, Analysis 2.6).…”
Section: Resultssupporting
confidence: 69%
“…Eleven trials were multi-armed, which led to 51 comparisons included in the review. We added five new trials in this current review update (Hop 2005; Giovannini 2006; Thi 2006; Esan 2013; Zlotkin 2013 (C)). We excluded 17 trials that assessed iron for the prevention or treatment of anaemia, which were included in the previous review version (Okebe 2011) from the current review update since they were conducted in hypoendemic or mesoendemic areas for malaria or provided an insufficient iron dose.…”
Section: Resultsmentioning
confidence: 99%
“…A more recent study among HIV-infected children in Malawi found that while iron supplementation improved hematologic indices, the risk of malaria was increased, postulated to be due to the utilization of free iron by Plasmodium species. 47 This theory was supported by another study in Tanzania, in an area of malaria transmission intensity similar to Uganda, in which researchers concluded that the risk of parasitemia was decreased, as was all-cause and malaria-specific mortality, among children with documented iron deficiency. 48 These studies support the role of screening for iron deficiency before supplementation and the relationship between iron metabolism and malaria.…”
Section: Discussionmentioning
confidence: 90%
“…While iron supplementation in eras with a higher burden of infectious diseases caused detrimental effects toward the risk of malaria or invasive bacterial infections (Sazawal et al, 2006; Soofi et al, 2013), iron supplementation in HIV infected patients resulted in an impaired control of malaria but also in a beneficial or at least neutral course of HIV infection at as reflected by CD4+-cell counts or progression of the disease which was partly dependent on the degree of anemia and base-line iron status (Esan et al, 2013; Prentice et al, 2013; Zlotkin et al, 2013). However, HIV infection is often associated with reactivation of Mycobacterium tuberculosis infection, and iron has been shown to be an essential nutrient for such bacteria which goes along with the observation that iron loading is associated with an increased risk for tuberculosis and an adverse clinical course of this infection (Moyo et al, 1997; Gangaidzo et al, 2001; Schaible and Kaufmann, 2004).…”
Section: Targeting Iron Homeostasis In Infectious Disease-to Walk a Tmentioning
confidence: 99%